Hubungan Status Ekonomi dan Tingkat Pengetahuan TB Dengan Keterlambatan Pasien Dalam Diagnosis Kasus TB Paru - Caesaria Sarah Selleca; Yusup Subagio Sutanto; . Reviono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Lately, there are a lot of TB cases with late diagnosis. Economic status and knowledge are one of many factor that could lead to late diagnosis in patient with pulmonary tuberculosis. This study aims to know the risk factors of economic status and knowledge to the incidence of TB patient with late diagnosis. Subject and Methods:This study used an observational analytic cross-sectional study approach (cross-sectional). It was held on May to August 2012 in Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta. The research subjects are 60 patient with new cases of pulmonary TB sampled by consecutive sampling method. The subjects were asked to answer a questionnaire about the late diagnosis, economic status (income) and the knowledge of TB. Data were analyzed using multiple linear regression analysis method (multivariate). Results:From 60 samples, there are 31 people with low economic status and 29 people with high economic status. Samples with high TB knowledge are 34 people and samples with low TB knowledge are 26 people. There are 38 people with late diagnosis and 22 people do not experience the late diagnosis. Economic status (income) has an effect on patient late diagnosis. Patients with lower incomes, on average, visit for the first time to a health facility 165.68 days slower than those with higher incomes (b: 165.68; 95% CI -33.21 s / d 364.56, p = 0.101) .Patients knowledge about TB also has an effect on patient late diagnosis. Patients with a low level of TB knowledge, on average, visit for the first time to a health facility 128.84 days slower than patients with high levels of TB knowledge (b: 128.84; 95% CI -71.73 s / d 329.40, p = 0.204). Conclusions:There is a relationship between economic status and level of knowledge of TB with patients delay, but the results were not statistically significant. Keywords: economic status, level of knowledge of TB, the patient delays